Holographic duals of M5-branes on an irregularly punctured sphere - Couzens, C; Kim, H; Kim, N; Lee, Y (Springer Nature, 2022)
We provide explicit holographic duals of M5-branes wrapped on a sphere with one irregular puncture and one regular puncture of arbitrary type. The solutions generalise the solutions corresponding to M5-branes wrapped on a disc recently constructed by Bah-Bonetti-Minasian-Nardoni by allowing for a general choice of regular puncture. We show that the central charges, flavour central charges and conformal dimensions of BPS operators match with a class of Argyres-Douglas theory.